Analysis of Waste of Customer Service Time for New Installations with a Lean Service Approach at PT XYZ - Floresta Andriano De Hautsmand; Enny Aryanny (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
Efficient water distribution is essential for public service, and PT XYZ faces significant challenges in its new customer installation process. The process, which involves several steps, experiences delays and inefficiencies that affect service quality. The research focuses on time waste during the customer installation process. Various forms of waste, such as delays, unnecessary movements, and redundant actions, lead to suboptimal service delivery. The aim is to identify sources of time waste and apply Lean Service principles to eliminate inefficiencies, thereby improving the customer installation process and enhancing overall service delivery. The study utilizes Lean Service tools, particularly Value Stream Mapping (VSM) and Process Cycle Efficiency (PCE) analysis, to assess the time spent on various activities within the installation process. Root cause analysis was conducted using Fishbone diagrams and the 5Whys method. The results from the current value stream mapping revealed that the total lead time for the process was 17.708 minutes, with value-added time of only 253 minutes, resulting in a Process Cycle Efficiency (PCE) of 1,4%. After improvements were implemented, the future value stream mapping showed a reduction in lead time to 14.828 minutes and an increase in value-added time to 253 minutes, improving the PCE to 1,7%. These improvements indicate better operational efficiency and resource optimization.